Evidence of chaos in eco-epidemic models - Dirk Stiefs; Ezio Venturino; Ulrike Feudel (Mathematical Biosciences and Engineering)
We study an eco-epidemic model with two trophic levels in which the dynamicsare determined by predator-prey interactions as well as thevulnerability of the predator to a disease. Using the concept ofgeneralized models we show that for certain classes of eco-epidemicmodels quasiperiodic and chaotic dynamics are generic and likely tooccur. This result is based on the existence of bifurcations of highercodimension such as double Hopf bifurcations. We illustrate theemergence of chaotic behavior with one example system.